Avoiding product abandonment through user centered design: A case study involving the development of a 3d printed customized upper limb prosthesis - Figliolia, Amanda [UNESP]; Medola, Fausto [UNESP]; Sandnes, Frode; Rodrigues, Ana Claudia Tavares; Paschoarelli, Luis Carlos [UNESP] (Springer Nature, 2020)
This study reports on experiences with a user centered design approach for the development of a customized mechanical transradial prosthesis for a patient who were unable to adapt to a standard prosthesis. The development process explored the needs, preferences and expectations of the user, as well as physical and functional aspects. The production process was based on 3D printing technologies, with emphasis on originality and customization. During the design process, the user participated in the design and evaluation phases through practical handling tests. The results indicated that the participation of the user in the design process using a user-centered design approach lead to a customized product that matched the user’s preferences. This acceptance and satisfaction with the product help minimize the risk of product abandonment.
Keywords: 3D printing; Assistive technologies; Collaborative design; Prosthesis; Upper limb